Photostability enhancement of an azobenzene photonic polymer - Galvan-Gonzalez, A; Belfield, KD; Stegeman, GI; Canva, M; Chan, KP; Park, K; Sukhomlinova, L; Twieg, RJ (AMER INST PHYSICS, 2000)
We have found that the presence of a methacrylate group on an azobenzene electro-optic chromophore can provide an enhancement in photostability of up to one or two orders of magnitude. Systematic studies involving the change in chromophore structure and atmospheric environment indicate that the photostabilization is due to antioxidant action by the unsaturated functional group. (C) 2000 American Institute of Physics. [S0003-6951(00)00540-4].
Keywords: NONLINEAR-OPTICAL CHROMOPHORES; PHOTODEGRADATION; STABILITY; PROGRESS